Augmented reality marketing in family ecotourism: Cognitive and behavioral drivers of destination branding - Iulian Adrian Sorcaru; Adrian Micu; Gianita Bleoju; Angela-Eliza Micu; George Bogdan Dragan; Mihaela-Carmen Muntean; Mark Anthony Camilleri (Journal of Innovation & Knowledge (JIK), 2025)
Most ecotourism destinations have not yet fully explored the benefits of augmented reality (AR) marketing in relation to family vacations. Although AR improves travel experiences and destination branding, there is limited research on parents' perceptions of AR when traveling with children. This study combines the unified theory of acceptance and use of technology (UTAUT) with the concept of sustainability education to investigate how parents' perceptions of AR technology shape visit behavior and destination branding, improve family vacations, and strengthen ecotourism sustainability. A mixed methods approach was applied, combining partial least structural equation modeling (PLS-SEM) with fuzzy-set qualitative comparative analysis (fsQCA). An online survey questionnaire (distributed via the Prolific platform) was completed by 181 parents who visited Romanian ecotourism destinations with their children and had previous AR experience. The PLS-SEM results indicate that facilitating conditions, performance expectancy, social influence, and sustainability education have significant effects on parents' intentions to use AR technology. Furthermore, these intentions significantly influence destination visit behavior and AR branding. The fsQCA results show that sustainability education is the sole necessary condition for AR technology to influence families' ecotourism experiences, possibly enhancing destination branding. The findings provide new theoretical and practical implications for ecotourism stakeholders interested in using AR to enhance their branding for families traveling with children.
Keywords: M31; Q55; Z33; 650; AR marketing; Augmented reality (AR); Destination branding; Ecotourism; Sustainability education; UTAUT